2022
DOI: 10.3389/fpsyg.2022.745259
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Challenge-Hindrance Stress on Employees’ Innovation Performance: A Chain Mediation Model

Abstract: Based on the transaction theory of stress and the theory of resource conservation, which introduces knowledge acquisition and intrinsic motivation as mediating variables, a chain mediating model for the influence of challenge-hindrance stress on innovation performance is constructed. Data of 295 samples collected in three stages were used to testify hypothesis. The results confirmed a positive relationship between challenge stress and innovation performance, and a negative relationship between hindrance stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…Challenge stress and hindrance stress We adopted the Challenge and Hindrance Stress Scale (CGSS) developed by Cavanaugh et al (2000). CGSS is a widely used scale with good reliability and validity (Cai et al, 2022;Liu, 2015;Yang et al, 2019;Zhang, Liu, Wang, & Qing, 2018). It had two subscales, one for challenge stress and the other for hindrance stress.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Challenge stress and hindrance stress We adopted the Challenge and Hindrance Stress Scale (CGSS) developed by Cavanaugh et al (2000). CGSS is a widely used scale with good reliability and validity (Cai et al, 2022;Liu, 2015;Yang et al, 2019;Zhang, Liu, Wang, & Qing, 2018). It had two subscales, one for challenge stress and the other for hindrance stress.…”
Section: Methodsmentioning
confidence: 99%
“…(2000). CGSS is a widely used scale with good reliability and validity (Cai et al., 2022; Liu, 2015; Yang et al., 2019; Zhang, Liu, Wang, & Qing, 2018). It had two subscales, one for challenge stress and the other for hindrance stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…But research stressing creativity is not very mature, and scholars often take stress as a negative factor affecting individual abilities. Indeed, there has been no consistent conclusion on the theoretical attributions, effects, and underlying mechanisms of different stressors affecting creativity ( Byron et al 2010 ; Cai et al 2022 ). Hon and Lui ( 2016 ) suggest that stress deserves more attention as a key factor in creativity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that challenge stress has a positive impact on an individual’s life, work, and personal growth ( Liu and Ren 2022 ; LePine et al 2005 ). In addition, challenge stress is a positive stressor that enhances innovation performance ( Cai et al 2022 ; Moin et al 2022 ). In terms of the reason why challenge stress affects creativity performance, from a psychological perspective, the Conservation of Resources (COR) Model indicates ( Halbesleben et al 2014 ) that individuals strive to protect their resources and obtain additional resources in all situations.…”
Section: Introductionmentioning
confidence: 99%